Tanoto Foundation Partner School Literacy Exploration : Best Practice Literacy of Elementary Education Students - Kiki Fatmawati; Desti Anggraini (Jurnal Paedagogy, 2023)
This research aims to explore the good practices of student literacy activities that have been done by Tanoto Foundation partner schools. This method of research used a descriptive with qualitative approach. The study involved informants who were at Tanoto Foudation partner schools, including principals, teachers and students. Data were collected with interviews, observations as well as documentation. Data analysis is carried out with descriptive qualitative including data collection, data presentation, data reduction and drawing conclusions. The results showed best practice that has been done by regional Tanoto partner schools in driving literacy, among others, providing literacy corners, scheduling literacy activities, reading books for 10-15 minutes, making wall magazines, bartering movements and donating books, holding and participating in literacy competitions and posting literacy activities outside. These findings offer good practice that can be an example in increasing literacy in schools.